GROWTH AND YIELD OF ORGANIC RICE WITH COW MANURE APPLICATION IN THE FIRST CROPPING SEASON - Sudarsono, Wahyu Arif; Melati, Maya; Aziz, Sandra Arifin (AGRIVITA Journal of Agricultural Science, 2014)
The study was addressed to investigating the effect of cow manure application rate on organic rice growth and yield in the first cropping season. The study was conducted from January to April 2012 in Blora, Central Java, Indonesia. The experiment was arranged in Randomized Complete Block Design, consisting of four treatments and four replications. There were two types of control treatments i.e. organic fertilizer treatments (statistically analyzed) and conventional fertilizer (not statistically analyzed). The treatments were corn biomass, corn biomass+cow manure (7.5 tons ha-1), corn biomass+cow manure (10 tons ha-1) and cow manure (10 tons ha-1) with square spacing of 20 cm x 20 cm. The organic control treatments were corn biomass+sheep manure (7.5 tons ha-1) with spacing of 20 cm x 20 cm and corn biomass+cow manure (7.5 tons ha-1) with double-row spacing of 40 cm x 25 cm x 15 cm. For every treatment, the rate of corn biomass was 3 tons ha-1. All organic treatments were also added with 3 tons rice hull ash ha-1. The application of cow manure (10 tons ha-1) with square spacing or corn biomass+cow manure (7.5 tons ha-1) with double-row spacing resulted in better performance than those of other treatments.Keywords: corn biomass, grumosol, organic farming, rice hull ash, sheep manure